Impact of IL-6 receptor inhibition on human memory B cells in vivo: impaired somatic hypermutation in preswitch memory B cells and modulation of mutational targeting in memory B cells. Issue 8 (8th May 2011) - Muhammad, Khalid; Roll, Petra; Seibold, Thomas; Kleinert, Stefan; Einsele, Hermann; Dörner, Thomas; Tony, Hans-Peter
Abstract : Objective: Interleukin 6 (IL-6) receptor (IL-6R) inhibition by tocilizumab is a novel anti-inflammatory therapy for rheumatoid arthritis (RA) patients. As IL-6 is a late differentiation factor of B cells the authors asked if IL-6R inhibition impacts on the mutational differentiation of human memory B-cell antigen receptors in vivo. Methods: 1733 immunoglobulin receptors (IgR) of single cell sorted preswitch and postswitch memory B cells were prospectively analysed from 11 RA patients under IL-6R inhibition (7 patients) or tumour necrosis factor (TNF) inhibition (4 patients). Results: The results show a reduced mutational frequency in IgR of preswitch memory B cells (p=0.0001) during week 12, week 24 and 1 year of tocilizumab therapy. Mutational hotspot RGYW/WRCY motifs indicated significantly decreased targeting (p<0.05) in preswitch and postswitch memory B cells. Anti-TNFα therapy had no effect on mutational frequency and mutational hotspot targeting motifs in memory B-cell subsets. Conclusions: These data suggest that preswitch and postswitch memory B cells are susceptible to IL-6R inhibition in vivo. Acquisition of mutations was substantially altered in preswitch memory B cells, while targeting of mutational hotspots affected preswitch and postswitch memory B cells. The results indicate that preswitch and postswitch memory B cells have a differential dependence on the IL-6/IL-6R system for differentiation, which can be influenced by tocilizumab in vivo.